Use of constructed wetland systems with Arundo and Sarcocornia for polishing high salinity tannery wastewater - Calheiros, Cristina S.C. (2012)
Treatment of tannery wastewater is problematic due to high and variable concentrations of complex pollutants often combined with high salinity levels. Two series of horizontal subsurface flow constructed wetlands (CWs) planted with Arundo donax and Sarcocornia fruticosa were set up after a conventional biological treatment system operating at a tannery site. The aim of the CWs was polishing organics and nitrogen from the high salinity effluent (2.2e6.6 g Cl L 1). Both plant species established and grew well in the CW. Arundo, however, had more vigorous growth and a higher capacity to take up nutrients. The CWs were efficient in removing COD and BOD5 with removal efficiencies varying between 51 and 80% for COD (inlet: 68e425 mg L 1) and between 53 and 90% for BOD5 (inlet: 16e220 mg L 1). Mass removal rates were up to 615 kg COD ha 1 d 1 and 363 BOD5 kg ha 1 d 1. Removal efficiencies were 40e93% for total P, 31e89% for NH4 þ and 41e90% for Total Kjeldahl Nitrogen. CW systems planted with salt tolerant plant species are a promising solution for polishing saline secondary effluent from the tannery industry to levels fulfilling the discharge standards.